PENGARUH DIVERSITAS DEWAN DIREKSI DAN KOMISARIS, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yusiresita Pajaria; Inten Meutia; Marlina Widiyanti (AKUNTABILITAS, 2016)
This study aimed to analyze the influence of diversity of boards of directors and commissioners consisting of gender diversity, diversity of nationalities, diversity education, firm size and profitability on the disclosure of Corporate Social Responsibility (CSR) .The manufacturing sector listed in Indonesia Stock Exchange 2011-2015 used as the sample in this study. Sample selection is done by purposive sampling method and acquired 42 companies with a number of observations as much as 210. The data analysis technique used is multiple linear regression analysis.Based Fhitung 0.001 0.001 with a significance of less than 0.05. This shows that all independent variables simultaneously is a significant explanatory on the dependent variable, so that the model used for the study worthy (fit). In a partial test (t test) to determine whether the independent variable Gender, ethnicity, education, firm size, and ROA  partially or individually CSR affect the dependent variable (Y),test results show that the diversity of gender, nationality, and the size of the company's influence on the disclosure of Corporate Social Responsibility (CSR). Meanwhile, educational diversity and profitability no influence on the disclosure of Corporate Social Responsibility (CSR).